ELASTISITAS HUKUM PIDANA ISLAM - Gustiawati, Syarifah (MIZAN: JOURNAL OF ISLAMIC LAW, 2013)
The Islamic Shariah is one aspect of the teachings of Islam’s universal and comprehensive. But this universality is often erroneously regarded by most people, especially the conventional legal experts. Islamic law is often viewed from one side only, without seeing the other side is not separate from the first side. Every time we heard the phrase ’Islamic law’, it is implied in their minds no more than a law cutting off hands, stoning, and qhisas which can be categorized as a ’verdict’. Though Islamic law is a revelation from God directly to arrange human life. Therefore, there are things that are elastic that is not rigid in its application.